2022
DOI: 10.1017/dmp.2022.207
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Artificial Intelligence for Twitter-based Public Discourse on Food Security During the COVID-19 Pandemic

Abstract: Objective: Food security during public health emergencies relies on situational awareness of needs and resources. Artificial intelligence (AI) has revolutionized situational awareness during crises, allowing the allocation of resources to needs through machine learning algorithms. Limited research exists monitoring Twitter for changes in the food security-related public discourse during the COVID-19 pandemic. We aim to address that gap with AI by classifying food security topics on Twitter and showing top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Martin et al [76] also found topics similar to those in our study, with food assistance, needs, and resources found to be the most dominant topic category, and these topics similarly discussed free food, donation, government assistance, food systems, and food banks. Martin et al [76] also highlighted the topic of emergency preparedness, which covered individual family crises, COVID-19-related food insecurity, and emergency aid in Tigray, all of which were discussed in tweets in our study. The time-series topic analysis by Benites-Lazaro et al [77] highlighted discussions on ethanol production (the topic of the study) and food security dominated by government bodies in comparison with nongovernment and media and peaking from 2007 to 2009, which aligned with the world food crisis.…”
Section: Comparison With Prior Worksupporting
confidence: 85%
See 2 more Smart Citations
“…Martin et al [76] also found topics similar to those in our study, with food assistance, needs, and resources found to be the most dominant topic category, and these topics similarly discussed free food, donation, government assistance, food systems, and food banks. Martin et al [76] also highlighted the topic of emergency preparedness, which covered individual family crises, COVID-19-related food insecurity, and emergency aid in Tigray, all of which were discussed in tweets in our study. The time-series topic analysis by Benites-Lazaro et al [77] highlighted discussions on ethanol production (the topic of the study) and food security dominated by government bodies in comparison with nongovernment and media and peaking from 2007 to 2009, which aligned with the world food crisis.…”
Section: Comparison With Prior Worksupporting
confidence: 85%
“…Our study found an increase in the popularity of food security conversations at the beginning of the COVID-19 pandemic, with similar findings related to frequency of discussion to those of Mayasari et al [75], who also found that Australia was among the top countries in search frequency regarding food security. Similarly, Martin et al [76] used topic modeling of tweets related to food security during the COVID-19 pandemic and found an increase in posts on food security, particularly related to food banks and food relief. Martin et al [76] also found topics similar to those in our study, with food assistance, needs, and resources found to be the most dominant topic category, and these topics similarly discussed free food, donation, government assistance, food systems, and food banks.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
See 1 more Smart Citation